Tree – ring growth response of scots pine (Pinus Sylvestris l.) to climate change / Nur Idzhainee Hashim, Rob Marrs and Nor Hanisah Mohd Hashim - Hashim, Nur Idzhainee; Rob, Marrs; Mohd Hashim, Nor Hanisah (Universiti Teknologi MARA, Negeri Sembilan, 2017)
Dendrochronology is the scientific discipline of determining the relationship between tree growth and climate , and is determined using the annual growth rings. This provides a potential method for monitoring climate change. Climate usually acts as a major factor influencing the tree growth. Here, the effects of climate of a conifer species was assessed in relation to measured climatic variables. Tree cores of Scots Pine (Pinus sylvestris) w ere sampled from a forestry plantation at Hordron Edge, Derbyshire to determine the relationship between ann ual growth incremen t and four climate variables (maximum temperature, minimum temperature, grass minim um temperature and rainfall). Standard dendrochronological techniques were used to collect, prepare and measure tree–ring width increments . Climate data were derived from the British Atmospheric Data Centre (BADC) from 1921–2013. Tree-ring widths were as cross referenced to the climate data to enable growth dynamics of (Pinus sylvestris) to be investigated. In this study there was no significan t correlation between growth and climatic variables; overall average mean sensitivity ( m s ) was 0.28 mm, only five of the 20 trees were sensitive to climate ( m s >0.3) with the other 15 trees being complacen t ( m s <0.3). The growth incremen t index p ortra yed a cyclic pattern of tree growth through time with peaks (fast growth) and troughs (slow growth) throughout the period. There were no significan t first-order relationships found between tree growth indices and any of the four climatic variables tested. This result suggests that cl ima t ic variables were not significan t in controlling tree growth at this site.